2013
DOI: 10.3109/03630269.2013.774283
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Rare β-Globin Gene Mutations in a Patient with β-Thalassemia Intermedia from Azerbaijan

Abstract: β-Thalassemias are an inherited group of disorders of hemoglobin (Hb) and comprise the most common monogenic disorders in Azerbaijan. They are extremely heterogeneous at the molecular level. Here we report the first identification of a patient who is a compound heterozygote for two rare β-thalassemia (β-thal) mutations, IVS-I-130 (G>C) and codon 37 (TGG>TGA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A number of studies revealed genotype-to-phenotype correlations of β-thalassemia mutations in various populations [ 17 , 18 , 19 ], and we hereby report the first one conducted in an Azerbaijani population. Recent studies reported 22 mutations of β-thalassemia in Azerbaijan, and it was found that the most common mutations among the Azerbaijani population are codon 8 (-AA), IVS-I-6 (T>C), and IVS-II-1 (G>A) [ 7 , 20 , 21 ]. The aim of our study was to investigate phenotypic manifestations of these three mutations by studying their hematologic parameters and clinical presentation in heterozygous, homozygous, and compound forms.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies revealed genotype-to-phenotype correlations of β-thalassemia mutations in various populations [ 17 , 18 , 19 ], and we hereby report the first one conducted in an Azerbaijani population. Recent studies reported 22 mutations of β-thalassemia in Azerbaijan, and it was found that the most common mutations among the Azerbaijani population are codon 8 (-AA), IVS-I-6 (T>C), and IVS-II-1 (G>A) [ 7 , 20 , 21 ]. The aim of our study was to investigate phenotypic manifestations of these three mutations by studying their hematologic parameters and clinical presentation in heterozygous, homozygous, and compound forms.…”
Section: Introductionmentioning
confidence: 99%